Expanding Horizon: Exploring Sustainable Movie Screening Venues for Student Films in Indonesia’s Evolving Exhibition Landscape - Amelia, Adilla; Meilani (Universitas Multimedia Nusantara, 2025)
Emerging new exhibition venues and platforms have created an evolving landscape of sustainable movie screening spaces for film students in Indonesia. Using descriptive research and observational methods this study aims to analyze multiple movie screening venues that can sustain film students’ showing. From the traditional theatrical exhibition spaces, alongside recent developments in the Indonesian film exhibition ecosystem. The research identifies six different screening space categories: commercial franchised theaters in major cities, regional cinema chains, serving smaller cities and regencies, privately owned community screening spaces, foreign cultural centers, subscription-based OTT services, and non-subscription streaming platforms. Exploring the geographic relationship between prominent film schools and these exhibition spaces, revealing new opportunities for student filmmakers outside of major cities with access to movie screening venues. The findings suggest that a hybrid exhibition strategy—combining intimate community screenings, regional theatrical exhibitions, and digital distribution—offers the most sustainable approach for student films, maximizing both audience reach and exhibition longevity. This research contributes to understanding how the democratization of screening spaces through both physical venues and digital platforms is reshaping opportunities for emerging Indonesian filmmakers in the post-pandemic era. Keywords: movie exhibition; screening spaces; sustainable distribution; student films, digital platforms